PENGEMBANGAN MEDIA E-STORY BOOK BERBASIS KEARIFAN LOKAL DALAM PEMBELAJARAN DONGENG SASTRA ANAK KELAS III SEKOLAH DASAR - Vina Aryani; Nur Fajrie; Lintang Kironoratri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research aims to develop digital media e-story book integrated with Grobogan local wisdom by analyzing the needs according to the characteristics of third grade students, testing the validity of the product and testing the effectiveness of using the media at SD N 1 Tuko in children's literature fairy tale material. The development research used the ADDIE model through five stages, namely: analyze, design, development, implementation and evaluation. The results of the development research showed that: (1) schools need digital media integrated with local wisdom to improve learning outcomes in the context of literacy in children's literary fairy tales; (2) validation by three material experts obtained an average score of 96.43% in the very valid category and validation by three media experts obtained an average score of 86.25% in the very valid category; (3) media implementation of limited scale product trials obtained an n-gain score of 0.72 in the high category to 5 students and an n-gain score of 0.73 in the high category of broad scale trials to 20 third grade students of SD N 1 Tuko so that e-story book products are effectively used as digital-based learning media to improve student literacy skills.